Manual of accounting : narrative reporting 2012 (Bloomsbury Professional West SussexGB)
Provides a practical guide to the legal and other regulatory requirements that impact elements of financial statements that are common to users of both IFRS and UK GAAP. Includes practical advice based on work in the PWC LLP's UK Accounting Consulting Services Team in advising the firm's clients, partners and staff. Deals with the requirements of the Combined Code on corporate governance and looks at the rules for the business review and expanded guidance on the operating and financial review. Also explained are the directors' report and their remuneration report.
Keywords: ACCOUNTING